A Large Randomized Trial: Effects of Mindfulness-Based Stress Reduction (MBSR) for Breast Cancer (BC) Survivors on Salivary Cortisol and IL-6. Issue 1 (January 2019) - Lengacher, Cecile A.; Reich, Richard R.; Paterson, Carly L.; Shelton, Melissa; Shivers, Steve; Ramesar, Sophia; Pleasant, Michelle L.; Budhrani-Shani, Pinky; Groer, Maureen; Post-White, Janice; Johnson-Mallard, Versie; Kane, Bradley; et al.
Breast cancer survivors (BCS) often experience psychological and physiological symptoms after cancer treatment. Mindfulness-based stress reduction (MBSR), a complementary and alternative therapy, has reduced subjective measures of stress, anxiety, and fatigue among BCS. Little is known, however, about how MBSR affects objective markers of stress, specifically the stress hormone cortisol and the pro-inflammatory cytokine interleukin-6 (IL-6). In the present study, BCS ( N = 322) were randomly assigned to a 6-week MBSR program for BC or usual-care control. Measurements of cortisol, IL-6, symptoms, and quality of life were obtained at orientation and 6 weeks. Cortisol and IL-6 were also measured prior to and after the MBSR(BC) class Weeks 1 and 6. The mean age of participants was 56.6 years and 69.4% were White non-Hispanic. Most had Stage I (33.8%) or II (35.7%) BC, and 35.7% had received chemotherapy and radiation. Cortisol levels were reduced immediately following MBSR(BC) class compared to before the class Weeks 1 and 6 (Wilcoxon-signed rank test; p < .01, d = .52–.56). IL-6 was significantly reduced from pre- to postclass at Week 6 (Wilcoxon-signed rank test; p < .01, d = .21). No differences were observed between the MBSR(BC) and control groups from baseline to Week 6 using linear mixed models. Significant relationships with small effect sizes were observed between IL-6 and both symptoms and quality of life in both groups. Results support the use of MBSR(BC) to reduce salivary cortisol and IL-6 levels in the short term in BCS.